Analisis dan Perancangan Perbaikan Sistem Perencanaan Produksi di PT. X - Robert Karyahastana; I Gede Agus Widyadana (Jurnal Titra, 2015)
PT. X is an company that focus on timber export production. PT. X suffers problem that there is no production planning document that can be checked which cause some delay in order to fulfill the due date of production activities. Besides, the company wants to establish PPIC Department and expects to standardize in all PPIC activities.Production planning system includes creating PPIC Department’s system, procedure and job description, making production planning module, making container setting module, and making production planning format.